Padronização de periódicos científicos on-line da área de Biblioteconomia e Ciência da Informação: adequação as normas ISO Standardization of on-line scientific periodic of the area librarianship and science of the information: adequacy norms ISO p.415-438 - Medeiros, Graziela Martins de; Fachin, Gleisy Regina Bóries; Rados, Gregório Jean Varvakis (Revista ACB, 2008)
Resumo:Reestruturar e adaptar o Modelo de Avaliação para Periódicos Científicos On-line. Fundamenta-se nas normas da International Organization for Standardization (ISO), tais sejam: ISO 9707/1991, ISO 20983/2003, ISO 8/1977 e ISO 215/1986. Especifica as variáveis das normas ISO que foram adaptadas e incluídas no Modelo, composto por nove critérios e 85 indicadores. Aplica o modelo em 17 periódicos científicos on-line da área de Biblioteconomia e Ciência da Informação. Analisa e discute os resultados para cada critério do Modelo e constata que os periódicos científicos on-line avaliados estão parcialmente normalizados. Conclui que os resultados obtidos poderão contribuir para a padronização e a recuperação dos periódicos científicos brasileiros e que os mesmos são preliminares, já que fazem parte de pesquisas em andamento, as quais visam à validação do Modelo em outras áreas do conhecimento. Abstract: It reorganizes the Model of Evaluation for Periodic Scientific On-line, developed for Fachin (2002) and adapted by Mendonça, Fachin and Varvakis (2006). It is based on the following norms of the International Organization for Standardization (ISO), such are: ISO 9707/1991, ISO 20983/2003, ISO 8/1977 and ISO 215/1986. It specifies the variable of the norms ISO that had been of enclosed in the Model, composition for nine criteria and 85 pointers. It was applied in 17 periodic scientific on-line of the area of Librarianship and Science of the Information. It analyzes and it argues the results for each criterion of evaluated the scientific Model and evidences that periodic on-line partially is normalized. It concludes that the gotten results will be able to contribute for the standardization and recovery of periodic the scientific Brazilians and that the same ones are preliminary, since they are part of research in progress, which aim at the validation of the Model in other areas of the knowledge.